ANALISIS KEMAMPUAN KONEKSI MATEMATIS BERDASARKAN TEORI KASTOLAN PADA SISWA KELAS IX - Aulia Sari; Rafiq Zulkarnaen (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2022)
Mathematical connections are one of the abilities that students must have. However, some studies showed that the students still lack abilities in mathematical connection. The aim of this study is to analyze and describe the types of errors and their factors based on Kastolan's theory. A case study is used in this research, with a single case and single analysis. The case in this study is the lack of students' ability in mathematical connection in solving problems regarding the material of a two-variable linear equation system (SPLDV), and single analysis is used to examine the factors that cause student errors in solving SPLDV questions. The subjects conducted 12 students of  IX grade in Islamic Junior High School Al-Ahliyah. The research instruments that are used by the writer are: a description test question which consists of three questions, and uses nonstructural interviews as a complement in collecting data. The data analysis technique is used in this study, such as: identifying, classifying, and analyzing student errors in answering questions based on Kastolan's types of errors; categorizing the percentage results based on the percentage of the types of Kastolan errors; and, drawing conclusions. The results of the study concluded that conceptual errors, procedural errors, and technical errors were the factors that caused the students to make mistakes, students are not able to manipulate the steps to solve problems, and especially students who were less thorough in solving the problems given, as for other factors in the learning process that was less than optimal.